METHODOLOGICAL ASPECTS OF DEVELOPMENT AND IMPLEMENTATION OF MANAGEMENT POLICY AT INDUSTRIAL ENTERPRISES - Natalia SKOROBOGATOVA (CES Working Papers, 2017)
The article examines the essence, main principles and objectives of the management policy at the enterprise. Author investigates in the position of management accounting in the enterprise management and structures the levels of management of the economic entity. A conceptual framework of management accounting has been developed in the paper, which includes the purpose, content, methods and results of the process of management accounting. On the example of the chemical industry, the international and domestic experience in the development and implementation of management policy within the structure of industrial enterprises were analyzed, as well as the positive and negative aspects of accounting practices were highlighted. Based on the analysis of foreign experience and taking into account the specificity of economic development of Ukraine, the author elaborates on the areas for the methodological approaches to the development of management policy of Ukrainian companies to be improved.